Behavior analysis of juvenile steelhead trout under blue and red light color conditions based on multiple object tracking - Li, Ziyu; Chen, Xueweijie; Huang, Jinze; An, Dong; Zhou, Yangen (Frontiers in Marine Science, 2024)
The lighting environment exerts a significant influence on fish behavior. To illuminate the mechanisms driving the impact of diverse lighting conditions on fish behavior, an inquiry was undertaken utilizing steelhead trout (Oncorhynchus mykiss) as a model species, focusing on the motion metrics of fish across different spectral conditions. In particular, this experiment was set up with six treatments at a constant light intensity of 150 lx: 12h white light + 12h dark (12 W), 12h blue light + 12h dark (12B), 12h red light + 12h dark (12 R), 1.5h blue light + 9h red light + 1.5h blue light + 12h dark (3B9R), 3h blue light + 6h red light + 3h blue light + 12h dark (6B6R), total 12h of blue and red light + 12h dark (T12BR). For the fish movement under the aforementioned conditions, a multiple object tracking method YOLOv5 with SORT was introduced to capture the movement trajectory of each individual fish, thereby quantifying three motion metrics swimming velocity, swimming angular velocity, and generalized intersection over union, as representations of fish behavior. The results revealed that fish exposed to 12R light environment showed significantly higher activity levels than other groups. The mixed light environments (3B9R, 6B6R) formed significant differences in behavioral metrics with 12R earlier than pure light environments (12B, 12W, T12BR). Fish in the 3B9R environment showed the lowest activity level and highest growth performance, indicating suitable for steelhead trout cultivation, but sudden light color changes should be avoided. This investigation delineates that behavioral disparities emerge notably earlier than physiological differentiations, manifesting as early as week eight. Substantial distinctions in growth patterns were observed by week 16, with the 3B9R treatment demonstrating the highest specific growth rate of 1.91±0.12 d -1 , a value significantly surpassing the lowest recorded rate, supported by a p-value of 0.0054. This paper used computer vision methods to analyze the influence of various light color combinations on fish behavior and determine the suitable light color environment for trout cultivation, offering a new perspective for light conditions and behavior in steelhead trout cultivation.